Fulani Herders – Farmers Conflict, ECOWAS Transhumance Protocol and Human Insecurity in The Sahel Region of Africa - Ohiri , Chinasa Agatha; Kazeem, Olayinka Sodik (PERSPEKTIF, 2024)
The movement of Fulani pastoralists and their cattle in search of greener pastures remains one of the most problematic security crises facing African countries. Despite spirited efforts at addressing this problem, several of these Fulani pastoralists have continued to refer to the old grazing routes, the ECOWAS Protocol on Transhumance (1998), ECOWAS Supporting Regulation (2003), and by extension the ECOWAS Protocol on Free Movement of Persons and Goods to justify their unregulated grazing. This has oftentimes led to confrontations among Fulani and host communities with grave human insecurity challenges.  Existing studies on the subject matter have focused on this human insecurity in a general sense and this justifies the need to interrogate other possible security threats occasioned by Fulani pastoralists and host communities fracas. Relying on secondary sources, this study argues that despite local initiatives to address these ongoing clashes, there have been more violent attacks in Africa especially in the Sahel region with no end in sight. Given the tendency for misinterpretation of these regional initiatives as a license for unregulated grazing, there is a compelling need for governments especially ECOWAS and the African Union to re-educate concerned parties about their salient points and workings as this remains the sine qua non for peace and stability across the region especially in the Sahel.